Human recombinant erythropoietin promotes differentiation of murine megakaryocytes in vitro. - Ishibashi, T (1987)
To determine if erythropoietin affects megakaryocytopoiesis, we measured acetylcholinesterase (AchE) activity, a marker of the murine megakaryocytic lineage, after the addition of human recombinant erythropoietin to serumless murine bone marrow cultures. Erythropoietin increased AchE activity substantially. Moreover, when the hormone was added to serumless cultures of 426 isolated single megakaryocytes derived from megakaryocytic colonies, erythropoietin induced a significant increase in the diameters of these cells. From a Bayesian analysis of the likelihood that some megakaryocytes increased in DNA content during the culture period, we estimate that 61% of the cells increased in ploidy. These data indicate that the action of erythropoietin is not restricted to the erythroid lineage.